Pain and delirium: mechanisms, assessment, and management - Sampson, Elizabeth L.; West, Emily; Fischer, Thomas (European Geriatric Medicine, 2020)
To provide a clinical overview of the association between pain and delirium, the mechanisms which may underlie this and how pain can be detected and managed in delirium.